Analysis of Islamic Education Methods - Siti Fatimatuzzahro; Rijalul Haq; Munazzah Hurun Ainun; Opik Taufik Kurahman; Tarsono Tarsono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic education methods according to Abdurrahman An Nahlawi in his work Usul At Tarbiyyah Al Islamiyyah Wa Asalibuha Fi Al Bayt Wa Al Madrasah Wa Al Mujtama’. Islamic education methods are understood as the means used by educators to instill the values of faith, morals, and knowledge based on the Qur'an and Sunnah. An Nahlawi proposed three main methods, namely Hiwar (conversation) which fosters interaction and critical thinking, Qudwah (exemplary behavior) which emphasizes the role of teachers and parents as moral models, and Mumarasah wa 'Amal (practice and practice) which connects theory with real practice. These three methods are considered relevant in contemporary learning because they are able to strengthen the teacher-student relationship, foster spiritual character, and integrate Islamic values in modern life.